Effect of Vitamin D supplementation on Insulin Resistance in Vitamin D-Deficient Obese Saudi Females; Randomized Controlled Trial - Noura S. Al-Mulhim; Rabia Latif; Lubna I. Al-Asoom; Ahmed A. Al-Sunni; Tharwat G. Eldin (Journal of King Abdulaziz University: Medical Sciences, 2023)
This study evaluates the effects of vitamin D supplementation on insulin resistance in vitamin D deficient obese Saudi females. Thirty vitamin D deficient obese female students were recruited from University of Dammam, Saudi Arabia and divided into a vitamin D group and a placebo group. Homeostasis model assessment of insulin resistance was compared between the groups and within the groups by two sample t test and paired t test, respectively. After treatment with 50,000 IU of vitamin D weekly for 8 weeks, the mean plasma levels of 25-hydroxy-vitamin D was significantly increased from 2.9 to 31.3 ng/ml in the vitamin D group. The results in the vitamin D supplemented group at baseline and at the end, for fasting plasma glucose were 97.90 ± 2.13 and 101.01 ± 1.67 mg/dl (P = 0.21), for insulin, 5.14 ± 3.22 and 4.68 ± 3.24 µIU/ml (P = 0.15) and for Homeostasis model assessment of insulin resistance, 1.28 ± 0.81 and 1.23 ± 0.87 (P = 0.62), respectively. This data showed insignifi cant changes in insulin resistance after treatment with vitamin D, suggesting that vitamin D supplementation may not have any eff ect on insulin resistance in vitamin D deficient obese females.